Item Analysis of Islamic Education For Class VIII at Junior High School 1 Jetis Ponorogo - Ihwan Mahmudi; Raden Rizky Fahrial Ahmad (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Education is a conscious activity that is intentional and planned to achieve a goal, then to achieve these objectives it is necessary to evaluate. The success of the evaluation activity can be seen from the making of questions, the implementation of the test and how the teacher can process the results of the test. The study’s aims to determine the quality of the items of the Midterm Exam for Islamic Religious Education 7th grade at Junior High School 1 Jetis Ponorogo 2019/2020 Academic Year in terms of validity, reliability, difficulty level, and different power. This research is a descriptive qualitative research. The object of this study is the Midterm Exam Subjects for Islamic Religious Education 7th grade at Junior High School 1 Jetis Ponorogo Academic Year 2019/2020 consisting of 20 multiple choice exam questions and 5 test items for essay/essay. The data collection technique this time uses the documentation method in the form of midterm examination scores. The results showed that: (1) the validity test, for multiple choice questions totaling 20 items in total was declared valid, as well as for the problem description / essay which totaled 5 items in total were declared valid. (2) the reliability test, in the form of multiple choice questions have a low reliability index of 0.654, as well as for the form of description / essay questions have a low reliability index of 0.529. (3) difficult level test, the form of multiple choice questions categorized as hard is 1 item (5%), 13 items (65%), easy 6 items (30%) and for the form of questions / essay questions are not available, while 3 items are (60%), easily 2 items (40%). (4) different power test problems, the form of multiple choice questions categorized as bad 6 items (30%), enough 13 items (65%), good 1 item (5%), very good none and for the form of question items / essays categorized as bad 1 item (20%), enough 2 items (40%), good 2 items (20%) absolutely nothing. (5) the quality of items in multiple choice questions including good quality is 14 items (70%), the quality is quite good 2 items (10%), and the quality is not good 4 items (20%) and for the description / essay questions included good quality is 3 items (60%), good quality is 1 item (20%), and quality is not good 1 item (20%). Based on the findings, then to improve the quality of the midterm examination even in the Islamic Religious Education subjects of 7th grade at Junior High School 1 Jetis Ponorogo, teachers should pay more attention to the item indicators both in terms of validity, reliability, difficulty level and different power of items to be tested.